Predictive Value of Preoperative Periocular Skin Cancer Measurements for Final Mohs Defect Size. Issue 6 (November 2019) - Scofield-Kaplan, Stacy M.; Jackson, Colette; Gurney, Troy; McDonnell, Emma; Mancini, Ronald
Abstract : Purpose: To evaluate the relationship between pre-Mohs skin cancer lesion measurements with the post-Mohs defect size in order to most accurately estimate post-Mohs defect size. Methods: This is a retrospective analysis of patients who underwent Mohs excision by one of 3 Mohs surgeons followed by reconstruction for basal cell carcinoma or squamous cell carcinoma of the eyelid. The study included all patients from January 2011 to May 2018 operated on by a single oculoplastic surgeon (R.M.) at the University of Texas Southwestern Medical Center. Maximum horizontal and vertical (H/V) dimensions were determined clinically by Mohs surgeons at the time of excision and photographs of the lesion and defect size were analyzed in order to determine the total area of the lesion preoperatively and the defect postoperatively with Image J using H/V dimensions and the area tracing function. Results: Forty-two patients with periocular skin cancers underwent Mohs resection followed by reconstruction. The Mohs defect was overall 4.88 times the size of the preoperative skin cancer measurement using maximum H/V dimensions by Mohs surgeons ( p < 0.0001). When using Image J, the area of the Mohs defect was 6.5 times the size of the preoperative lesion ( p < 0.0001) using both the maximum H/V dimensions and the area tracing function. There was a statistically significant difference between the Image J area tracing and area determined with H/V dimensions by both the Mohs surgeon and Image J. Conclusions: Postoperative Mohs defect size can be estimated based on maximum H/V dimensions clinically or with Image J technology. Image J digital photograph analysis using the area tracing function more accurately determines the pre-Mohs lesion size and the post-Mohs defect area when compared with standard maximum H/V measurements and digital photographic analysis of maximum H/V measurements with Image J. The preoperative periocular skin cancer measurements can assist in determining the post-Mohs defect size.